Intellectual property agreements, ¿Do they bring us closer to development? (2011)
This document makes an analysis of intellectual property from its origins to the chapters in Free Trade Agreements (WIPO-plus), which includes a review of the role of different international organizations concerned with intellectual property, a review of discussions that are at the origin of the WTO inmatters related to intellectual property (TRIPS), an analysis of intellectual property as a market failure. We propose that Intellectual Property has evolved from inexistent protection to rigid legislation that favors the interests of the economies of economic powers. It also suggests that the evolution of the Intellectual Property system contradicts the initial objectives of promoting scientific production, artistic creation and transfer of  technology to promote development, turning it into a monopoly of knowledge